(untitled) (Conferencea, 2022)
From the earliest descriptions of patients with pulmonary fibrosis, cellular inflammation in the lung parenchyma has been a consistent pathologic finding . Histologic analysis has shown varied accumulations of lymphocytes, macrophages, plasma cells, eosinophils and neutrophils, and the presence of lymphoid follicles with germinal centers has been observed in many patients in the lung interstitium . The initial terms ‘diffuse fibrosing alveolitis’ and ‘cryptogenic fibrosing alveolitis’ were used as a reflection of the inflammatory component of the pathologic process in pulmonary fibrosis , and most patients with usual interstitial pneumonia (UIP), the pathologic hallmark of IPF, will manifest a mild to moderate degree of chronic cellular inflammation in the lung.